Dualistic Common Mode Outage Model for Reliability Assessment of Composite Power System - Babu kathi, Venkatasatheesh; Vellala, Madhusudhan; Vulasala, Ganesh (International Journal of Engineering and Technology, 2018)
Composite power system reliability estimation is gaining attention of researchers due to the rapid growth in interconnected networks. Traditional methods deploy independent outage model for reliability studies. Globally, climate changes are inevitable as hurricanes, tornados and other environmental factors are not under system operator control. As the transmission lines are exposed to environment the model chosen for reliability studies must account for common mode outages involving multiple outages owing to single triggering event. This paper investigates the consequence of common mode outages on composite power system reliability. A dualistic model for common mode pair of transmission lines was adopted for system studies. The proposed methodology is more pragmatic for messily interconnected systems like Indian grids. Reliability experimental networks like RBTS-6 node network and RTS-24 node networks were deployed to validate the methodology.Â Â